2020
DOI: 10.1039/d0ta01559h
|View full text |Cite
|
Sign up to set email alerts
|

Advances in tuning the “d33 ∝ 1/Td” bottleneck: simultaneously realizing large d33 and high Td in Bi0.5Na0.5TiO3-based relaxor ferroelectrics

Abstract: We report the simultaneous achievement of a large d33 and a high depolarization temperature (Td) in Bi0.5Na0.5TiO3-based complex oxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…7,8,15,16 While the MPB compositions exhibit the highest piezoelectric and coupling coefficients, their lower depolarization temperature is a limiting drawback in applications demanding higher operational temperatures. 11,17,18 NBT-BT has distinct advantages when contrasted to PZT. Tou et al, 19 Doshida et al, 20 and Hejazi et al 21 demonstrated that NBT-based materials can withstand high vibration velocity and even outperform PZT-based materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,15,16 While the MPB compositions exhibit the highest piezoelectric and coupling coefficients, their lower depolarization temperature is a limiting drawback in applications demanding higher operational temperatures. 11,17,18 NBT-BT has distinct advantages when contrasted to PZT. Tou et al, 19 Doshida et al, 20 and Hejazi et al 21 demonstrated that NBT-based materials can withstand high vibration velocity and even outperform PZT-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…The transition was reported to be positioned between NBT‐6BT and NBT‐7BT, and the inconsistency in the criticality can be assigned to different processing conditions and the resulting small deviations in stoichiometry and microstructure 7,8,15,16 . While the MPB compositions exhibit the highest piezoelectric and coupling coefficients, their lower depolarization temperature is a limiting drawback in applications demanding higher operational temperatures 11,17,18 …”
Section: Introductionmentioning
confidence: 99%
“…The above analysis indicated the transformation of the BS‐xPT‐BSN ceramics from relaxed ferroelectric to normal ferroelectric, which means that the short‐range order in ceramics was gradually destroyed as the PT content increased following the formation of the long‐range order 21 . As shown in Figure 3F, the room temperature permittivity reduced as the PT content increased, which also confirmed the formation of the long‐range order 22 . Additionally, the long‐range order affected the activities of the domain and domain wall, which were closely related to the electrical performance.…”
Section: Resultsmentioning
confidence: 61%
“…21 As shown in Figure 3F, the room temperature permittivity reduced as the PT content increased, which also confirmed the formation of the long-range order. 22 Additionally, the long-range order affected the activities of the domain and domain wall, which were closely related to the electrical performance. The details are introduced in the next section.…”
Section: Methodsmentioning
confidence: 99%
“…28,34 Piezoresponse force microscopy (PFM) shows a morphology change from labyrinth-like structures towards an increased area and width of the domains in quenched NBT-based ceramics. 35 The NBT-BT solid solution undergoes several temperature-induced phase transitions depending on the composition. In pure NBT, a R3c to P4bm transition starting at ∼255 • C and a P4bm to Pm 3m transition starting at ∼500 • C was reported based on powder neutron diffraction.…”
Section: Introductionmentioning
confidence: 99%